Ostracoda non-marine biogeography in Campanian-Maastrichtian ages: South America, Africa and India connections - Gobbo, Silvia Regina [UNESP]; Bertini, Reinaldo J. [UNESP] (Elsevier, 2023)
Non-marine ostracods from the Upper Cretaceous of Southern Hemisphere (South America, Africa and India) are studied and discussed for the purpose of establishing a biostratigraphy scheme and their paleogeographic distribution. The paleogeographic analysis performed here reveals ten distinct groupings of species: (1) Neuquén and Paraná basins (Brazil) are characterized by Ilyocypris riograndensis, Neuquenocypris minor, Neuquenocypris tenuipunctata, Wolburgiopsis vicinalis and Vecticypris aff. punctata; (2) Wolburgiopsis neocretacea is characteristic of Los Llanos Formation (Sub-Andean Basin, Argentina) and Neuquén (Argentina) and Parana basins (Brazil); (3) Ilyocypris triebeli is characteristic of Sub-Andean Basins (El Molino Formation, Bolivia; Los Llanos, Ciénaga del Rio Huaco formations, Argentina), and Yacoraite formations (Salta Basin); Neuquén (Argentina), Paraná and Campos basins (Brazil): Ilyocypris triebeli; (4) Neuquén (Argentina), Paraná and Santos basins (Brazil): Fossocytheridea lobulata; (5) Paraná, Santos (Brazil), Congo (R. D. Congo) basins and Lameta Formation (India): Stenocypris cylindrica; (6) Paraná (Brazil) and Congo (R. D. Congo) basins: Paracypria makawensis and Species “K 530 b” Grekoff, 1960; (7) Yacoraite Formation (Salta Basin) and Neuquén Basin (Argentina), Paraná (Brazil) and Congo (R. D. Congo) basins: Ilyocypris argentiniensis; (8) Neuquén (Argentina), Paraná (Brazil) and Congo (R. D. Congo) basins: Alicenula kwangoensis; (9) Paraná Basin (Brazil) and Lameta Formation (India): Candona chuiensis, Cypridopsis huenei, Paracandona jabalpurensis and Paralimnocythere hasuii; (10) Paraná (Brazil), Congo (R. D. Congo) basins and Lameta Formation (India): Periosocypris megistus. Other generic correlations, especially the genera Wolburgiopsis, Neuquenocypris, Virgatocypris, Altanicypris and Talycypridea, reinforce this paleobiogeographical similarities and a Campanian-Maastrichtian age to the Bauru Group (Paraná Basin) and the Kwango Series (Congo Basin), whose age was still in need of refinement.
Keywords: Biostratigraphy; Continental environments; Gondwana; Ostracoda; Upper cretaceous